2022
DOI: 10.1186/s12866-022-02656-1
|View full text |Cite
|
Sign up to set email alerts
|

Visual LAMP method for the detection of Vibrio vulnificus in aquatic products and environmental water

Abstract: Background A visual, rapid, simple method was developed based on a loop-mediated isothermal amplification (LAMP) assay to detect Vibrio vulnificus in aquatic products and aquaculture waters. Results Genomic DNA was extracted from Vibrio vulnificus using the boiling method, and optimized primers were used to detect the gyrB gene using a visual LAMP method. The sensitivity of the assay was 10 fg/μL, and the obtained results were stable and reliable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This indicates that Tt values were minimally affected by the amount of DNA used, suggesting that the amplification reaction approached saturation at 25 ng of DNA. Tian et al [27] reported that the sensitivity of LAMP targeting V. vulnificus gyrB was only 10 fg/µL. Although we did not carry out a sensitivity test, the sensitivity of LAMP targeting vvhA may be comparable at a similar concentration.…”
Section: Development Of a Genotype-specific Lamp Methods Targeting Vvhamentioning
confidence: 75%
See 1 more Smart Citation
“…This indicates that Tt values were minimally affected by the amount of DNA used, suggesting that the amplification reaction approached saturation at 25 ng of DNA. Tian et al [27] reported that the sensitivity of LAMP targeting V. vulnificus gyrB was only 10 fg/µL. Although we did not carry out a sensitivity test, the sensitivity of LAMP targeting vvhA may be comparable at a similar concentration.…”
Section: Development Of a Genotype-specific Lamp Methods Targeting Vvhamentioning
confidence: 75%
“…Taken together, it may be concluded that the LAMP method targeting vvhA is specific to V. vulnificus and suitable for genotyping bacterial species. Although several researchers have developed LAMP methods targeting vvhA or other genes [27][28][29], none have been applied to differentiate V. vulnificus isolates into genotypes.…”
Section: Development Of a Genotype-specific Lamp Methods Targeting Vvhamentioning
confidence: 99%
“…Currently, the target genes used for molecular diagnosis of Vibrio species mainly include speci c independent genes, such as the thermostable direct hemolysin (tdh) gene, TDH-related hemolysin (trh) gene, thermolabile hemolysin (tlh) gene, and toxR gene, which encodes the transmembrane transcription regulator (Vuddhakul et with the enrichment of genomic databases, the gyrB gene has been found to be signi cant for distinguishing closely related species (Liu et al 2021). The gyrB gene is a commonly found single-copy gene in bacteria that encodes the DNA gyrase B subunit protein, which plays an important role in the DNA replication process (Tian et al 2022). As a housekeeping gene in bacteria, the gyrB gene is widely present and maintains the basic functions of bacteria.…”
Section: Validation Of Wild Strainsmentioning
confidence: 99%
“…al. 2000;Tian et al 2022). Housekeeping genes such as 16S ribosomal RNA (16S rRNA) and the gyrB gene(Vuddhakul et al 2000;Liu et al 2021) are also used.…”
mentioning
confidence: 99%
“…Before our study, LAMP was used for V. vulni cus rapid detection by targeting a variety of speci c genes, such as gyrB, rpoS, and vvha. Zhou et al aimed at the gyrB gene of V. Vulni cus performing a 34 min LAMP detection, and the LOD was 10 fg/µL, the results of which indicated high sensitivity and a shorter time than that of other PCR methods for V. Vulni cus detection(Tian et al 2022). A rpoS-based 90-min LAMP assay was developed by Surasilp et al reporting a LOD of 1.5×10 3 CFU/mL(Surasilp et al 2011), which was signi cantly improved in the sensitivity and detection time compared with the traditional PCR method.…”
mentioning
confidence: 99%